The PENGARUH KINERJA LINGUNGAN, BIAYA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN (Studi Kasus pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia Terdaftar di Bursa Efek Indonesia Periode 2020-2022): KINERJA LINGUNGAN, BIAYA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Bartolome, Erdy Ismail; Khairin, Fibriyani Nur; Bartolome, Erdy Ismail Bartolome (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2025)
This study aims to analyze and describe the effect of environmental performance, environmental costs, and company size on financial performance. i This study used a purposive sampling method and obtained 11 company samples with a total of 33 company data from 92 manufacturing companies in the basic and chemical industry sectors listed on the Indonesian stock exchange in the period 2020-2022. The data analysis techniques used are quantitative methods with descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, coefficient of determination tests, and hypothesis tests consisting of the F test and t test. The results of the analysis show that environmental performance has no significant and negative effect on financial performance, while environmental costs have a significant and negative effect on financial performance, and company size has a significant and positive effect on financial performance